Dealer Pricing of Consumer Credit - Giuseppe Bertola; Stefan Hochguertel; Winfried Koeniger (Institute for the Study of Labor (IZA), 2002)
Interest rates on consumer lending are lower when funds are tied to purchase of a durable good than when they are made available on an unconditional basis. Further, dealers often choose to bear the financial cost of their customers? credit purchases. This paper interprets this phenomenon in terms of monopolistic price discrimination. We characterize consumers? intertemporal consumption decisions when their borrowing and lending rates are different not only from each other, but also from the internal rate of return of financing terms for a specific durable good purchase. A stylized model offers a closed-form characterization of purchase decisions as a function of the amount and timing of consumers? resources, of the spread between the borrowing and lending rates, and of the pricing of cash and credit purchases. We then study theoretical and empirical relationships between the structure of financial markets, the distribution of potential customers? current and future income, and incentives for durable-good dealers to price-discriminate by subsidizing their liquidity-constrained customers? installment-payment terms. Our empirical analysis takes advantage of a rich set of installment-credit and personal-loan data, which offer considerable support for the assumptions and implications of our theoretical perspective.
Keywords: D10; G2; D42; 330; Price discrimination; financial market development; liquidity constraints; Verbraucherkredit; Kreditgeschäft; Finanzdienstleistung; Dauerhaftes Konsumgut; Preisdifferenzierung; Verschuldungsrestriktion; Theorie